IMPLEMENTASI METODE TILAWATI DAN METODE IQRO’ DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN - Nurhayah Nurhayah; Muhajir Muhajir (QATHRUNÂ, 2020)
This study aims to describe the implementation of the tilawati method and the iqro 'method, the students' reading ability of al-Qur'an, the factors supporting and inhibiting the implementation of the tilawati method and the iqro 'method, and the differences in the implementation of the tilawati method and the iqro method'. This type of research is field research (field research) with qualitative descriptive analytic research methods. The results of the research are as follows: 1) the implementation of the tilawati method in Al-Azhar Islamic Elementary School was carried out through the tilawati habituation program in the morning for three days for 30 minutes, and the ATQ (Al-Azhar Tilawatil Qur'an) activity. While the implementation of the method of iqro'in SDIT Nur El-Qolam is carried out through the tasmi program 'for three days for 30 minutes, and learning iqro' in class for 90 minutes and two meetings a week; 2) the ability to read al-Qur'an students of Al-Azhar Islamic Elementary School and SDIT Nur El-Qolam students are divided into very good, good, and sufficient categories; 3) supporting factors for the implementation of the tilawati method in Al-Azhar Islamic Elementary School: the existence of school policies, tilawati schedules, guidance and training for tilawati teachers, student interest, and infrastructure. While the obstacles are students who do not focus on meditation, lack of time allocation, and parental awareness is still low. The supporting factors for the implementation of the iqro 'method at SDIT Nur El-Qolam are the existence of school programs, the existence of musyrif, the existence of the iqro' method of talaqi program for teachers, and the appropriateness of using the iqro book '(at home and at school), and the active role of the teacher. Meanwhile, the obstacles are lack of student discipline in class, busy parents, and the impact of technology; 4) The difference in the implementation of the tilawati method found in Al-Azhar Islamic Elementary School lies in the seating arrangement of students, guidance at each stage, the use of the rost song, the classical system, and reading (the truth in reading), and the increase in student volumes is measured by group ability. . Meanwhile, the iqro 'method at SDIT Nur El-Qolam emphasizes makhraj and tajwid, fluency, fluency, independence in reading learning activities (CBSA), and volume increase to see the individual abilities of students.